Standardization of Modified Dosage Form of Lodhradi Kashaya Prepared by Two Different Techniques - Reddy, K. R. C. (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: Time‑dependent advancement in dosage form has been required to stay in competitive market and to provide ease of administration to the patients. Standardization, a tool to ensure quality and safety among consumer is primary concern during the preparation of any drug. Lodhradi Kashaya (formulation mentioned in Basavarajiyam and Vaidya Chintamani for diabetes mellitus) is decoction dosage form, so the demand versus supply has been questioned against its stability period. Hence, modification in the dosage form was attempted to ensure stability period, and thus, powder dosage form has been prepared. Aim: Standardization of modified dosage form of Lodhradi Kashaya has been done to ensure quality of finished drug. Materials and Methods: Two sample were prepared, one is by following the traditional method of Ayurveda followed by drying and grinding to get fine powder (LKLB). In second sample decoction was prepared by following continuous aqueous extraction and dried with spray drier technology to get fine powder (LKSD). Both the samples were standardized over several physicochemical testing, organoleptic properties along with microbial load and heavy metal content. Results: The comparative result was interpreted in this paper, major highlight are color and fineness of both powder was found different. No much variation in the physicochemical parameter. Microbial load of LKLB was much higher than LKSD but found within limit. Heavy metal content was found within the limit prescribed in The Ayurvedic Pharmacopoeia of India. Conclusion: Both the samples were standardized and quality of the modified dosage form of Lodhradi Kashaya has been assured.